From Oral Epic to the Written One: on One Type of Formulae in P. A. Oyunsky’s Olonkho “Nyurgun Bootur the Swift” - Pokatilova, Nadezhda Volodarovna; Orosina, Nadezhda Anatolyevna (Journal of History Culture and Art Research, 2018)
Typology of differentiation between oral and literary eposes developed according to different traditions and was based on a variety of materials (M. Parry, A. Lord, A.N. Veselovsky, V.M. Zhirmunsky, M.I. Steblin-Kamensky, E.M. Meletinsky and others). Formulaicity remains one of the indicators of similarities and distinctions between the two types of epos – oral and written. The term was introduced by M. Parry and A. Lord; however, the problem of the nature and characteristics of formulaicity remains arguable under traditions which vary in their origins. Olonkho by one of the first Yakut authors, P.A. Oyunsky allows one to trace the process of creation and producing of formulae within the space of an epic text of written origin. The author’s epos includes the types of formulae in which narrator’s personal name becomes a key element in not only creating alliteration, but also for unfolding the poetic meaning of the entire epic phrase. The analysis shown in the article indicates that despite the similarity in structure, each time the formula re-creates characteristic feature of a certain narrator’s performance. This is an evidence of the name formulae of the type considered here being the symbol of the rising outside (“outside” of the culture) outlook from the writer on formulaicity in oral tradition. It is also shown that a written-origin epos is also characterized by formulaicity while the rules and mechanisms of its producing visibly differ from formulaicity of oral epos. The type of formulae considered presents author’s poetic expression of their attitude to the preceding tradition of narrating. These formulae also allow (within their limits) a reconstruction of the epic environment. It is concluded that the distinction of the naming formula is not only limited to alliterating narrator’s personal name. It also gives meaning to a trope (periphrasis, metaphor, simile) linked to the characteristics of narrator’s unique manner.